Induced breeding of Indian carps using Des Gly^10 [D-Ala^6] LHRH ethylamide - and Sebastian, Jose, T.M. Mohan, M.V. (Fishery Technology, 2021)
Details are given of a study conducted in order to determine the efficacy of Des Gly^10 [D-Ala^6] LHRH ethylamide in the induction of spawning in Cirrhinus mrigala and Labeo fimbriatus . Findings shows this LHRH analogue to be a promising substitute for the pituitary gland extract which is currently used. Further studies are required to standardize the dose and method of administration in the various cultivable species in India.